Respuesta :
Answer:
9
Step-by-step explanation:
[tex]p(y)=y^3+3y^2-5y-6 \\\\p(-3)=(-3)^3+3(-3)^2-5(-3)-6= \\\\-27+27+15-6= \\\\9[/tex]
Hope this helps!
Answer:
p(-3)=9
Step-by-step explanation:
This question ask us to find p(-3), or what p(y) is when y is equal to -3.
We know that:
p(y)= y^3+3 y^2-5y-6
We want to find p(-3), so substitute -3 in for every y.
p(-3)= (-3^3)+3(-3^2)-5(-3)-6
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction.
Solve the exponents first (-3^3 and -3^2)
-3^3=-3*-3*-3= -27
-3^2= -3* -3= 9
p(-3)= -27+ 3(9) -5(-3) -6
Next, multiply 3 and 9
p(-3)= -27+27-5(-3)-6
Then, multiply -5 and -3
p(-3)= -27+27+15-6
-27 and 27 equal 0, so they cancel each other out.
p(-3)=15-6
p(-3)= 9